2019
DOI: 10.3390/app9214691
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Molecular Polarizability and of Intensity Carrying Modes Contributions in Circular Dichroism Spectroscopies

Abstract: We re-examine the theory of electronic and vibrational circular dichroism spectroscopy in terms of the formalism of frequency-dependent molecular polarizabilities. We show the link between Fermi’s gold rule in circular dichroism and the trace of the complex electric dipole–magnetic dipole polarizability. We introduce the C++ code polar to compute the molecular polarizability complex tensors from quantum chemistry outputs, thus simulating straightforwardly UV-visible absorption (UV-Vis)/electronic circular dich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 88 publications
(152 reference statements)
0
9
0
Order By: Relevance
“…In the Appendix 1, it is shown that for a given applied field F , the equilibrium positions of the atoms in the molecule change along each normal coordinate according to The combination of eqs and leads to the first-order field-dependence of the dipole that includes the effects of molecular structure relaxation through the so-called vibrational polarizability α r ( 0 , 0 )­ The expression of vibrational polarizability α r given by eq matches those obtained by different approaches in the past (see for instance refs ). Clearly, based on eq , when applying an electric field F , the molecular dipole changes according to an effective polarizability, which is given by the sum of the electronic polarizability α e ( 0 , 0 ) (clamped nuclei) and the vibrational polarizability α r ( 0 , 0 ) that accounts for the relaxation of the molecular structure.…”
Section: Theoretical Frameworkmentioning
confidence: 67%
“…In the Appendix 1, it is shown that for a given applied field F , the equilibrium positions of the atoms in the molecule change along each normal coordinate according to The combination of eqs and leads to the first-order field-dependence of the dipole that includes the effects of molecular structure relaxation through the so-called vibrational polarizability α r ( 0 , 0 )­ The expression of vibrational polarizability α r given by eq matches those obtained by different approaches in the past (see for instance refs ). Clearly, based on eq , when applying an electric field F , the molecular dipole changes according to an effective polarizability, which is given by the sum of the electronic polarizability α e ( 0 , 0 ) (clamped nuclei) and the vibrational polarizability α r ( 0 , 0 ) that accounts for the relaxation of the molecular structure.…”
Section: Theoretical Frameworkmentioning
confidence: 67%
“…Furthermore, since its publication in 2018, 17 separate projects to date have leveraged the Psi4NumPy framework to facilitate their development of novel quantum chemical methods. [101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117] Finally, Psi4NumPy is a thoroughly community-driven project; interested readers are highly encouraged to visit the repository 100 for the latest version of Psi4NumPy and to participate in "pull request" code review, issue tracking, or by contributing code to the project itself.…”
Section: A Psi4numpymentioning
confidence: 99%
“…The static spectrum of the gas-phase isolated 1S-FEN molecule discussed in the next section was computed with the Gaussian16 code, VCD package, , in the double harmonic approximation. Previous works have shown that the B3LYP functional , with the aug-cc-TZvp bais set , allows for correctly reproducing all the main features of the experimental spectrum in the fingerprint region. Therefore, the same computational setup was adopted here.…”
Section: Benchmarkmentioning
confidence: 99%
“…Due to the variety and complexity of the factors interplaying in determining the spectral shape, the interpretation of spectroscopic data based on experimental measurements alone can lead to uncertainties and ambiguities. In this respect, theoretical calculations are a powerful tool for analyzing the connection between structure and spectroscopic marker bands. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation